Collaborating with competitors : value through coopetition in the New Zealand forest industry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Supply Chain Management at Massey University, Manawatu, New Zealand - Christians, Virginia Anne (Massey University, 2016)
The purpose of this research is to investigate the scale of possibility for coopetition to be applied to the logistics activities in the export log supply chain in New Zealand. The research ascertains there are financial benefits of approximately $200million to the industry from cooperating in port logistics and shipping activities while continuing to compete in other sectors of the chain. The research tests to see if the existing theory on barriers and facilitators applies in this case study. Two research methods were used: 1. Qualitative interviews with exporters to probe for specific factors that support or hinder coopetition adaptation. 2. Quantitative research looking at financial implications, involving data collection from industry, building a simulation model, and simulating four degrees of coopetition adoption. The research identifies that small levels of cooperation between exporters can produce the most cost reduction benefits, with decreasing returns to scale through further collaboration attempts. As well as providing overall cost reductions the research indicates that there is a significant reduction in cost volatility by collaboration in shipping and logistics. While exporters used various terminology the themes that emerged, through semi-formal interviews, the barriers and enablers that were identified in this context relate closely to those models of other authors. The alignment of the physical world in time and space, the connection between strategic business models and relevant levels of autonomy and risk and the alignment of values, history and ability to communicate with relationship and their cost were all found to be significant factors that could both enable or disable cooperation between competitors in this case. Levels of trust and communication were found to be generally low in the log export industry the input of an independent third party may assist in supporting cooperation. The research concludes that there is potential for at least small and medium sized players in the industry to adopt some level of coopetition to reduce costs in the supply chain. However, the findings indicated that there are significant invisible costs associated with coopetition outside of the operational costs. The full cost of building and maintaining relationships required for it to persist still needs to be investigated further. These factors should be considered when analysing the savings as they may easily erode any gains made through coopetition.
Keywords: Forests and forestry; Cooperation; Competition; Coopetition; Business logistics; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies